ANTI-AMNESIA:E-MARKETPLACE AS A MEDIATOR TO PRESERVE TRADITIONAL INDUSTRIES - Silva, Sara Alexandra Lopes da (2021)
Traditional industries in Portugal face challenges that compromise their economic viability, such as apathy from younger generations and an increased incompatibility with the new technologies, that can potentially cause the dissipation of these practices and traditions as a reliable source of income. This research aims to contribute to the preservation and revitalization of these crafts through an electronic marketplace that concentrates consumers and merchants in the same ecosystem, encouraging artisans to shift and expand their sales channel in a low-risk online scenario. The practical development of this platform started with a market research and literature review to understand the current situation and execute a benchmarking analysis with two national references. This inspired the definition of the target audience divided into two archetypes (buyer and seller), followed by the information architecture, user flows and the taxonomy for the website. Two prototypes were developed to explore the user experience of both personas using a user-centered approach, where the principles of UI/UX were implemented to better understand the needs of end-users and explore all the design solutions to create a very intuitive website. The high-fidelity prototypes were tested with a representative sample with a realistic scenario of tasks to complete to collect feedback that, overall, was very positive. The users were encouraged to comfortably make their suggestions during the entire process, in an attempt to improve the user experience of this electronic marketplace, regardless of the digital literacy level of the user.